Getting the most out of the research experience : what every researcher needs to know - Roberts, Brian, 1950- (SAGE Publications, 2007)
Brian Roberts takes the researcher through the research process answering the practical and subjective questions anyone will face, on issues like: entering the field and emotional aspects of research, types of research and associated experiences writing and research 'blocks' and 'research confessions'.